Theorical approaches to the relationship between csr and competitiveness: inicial paths (2020)
Today’s markets are characterized by high levels of competitiveness among participants, forcing business to innovate ways to meet the needs and / or desires. This leads to new relationships between companies and all those affected in the process of production of the good or service provision. This advance aims to show the state of the question about research, establishing some relationship between CSR and competitiveness. The initial conclusion is that there is a tendency to consider that there is a positive relationship, however this varies according to the interest group which is inquire and / or country and / or sector of economic activity being studied